2017
DOI: 10.1128/mbio.00413-17
|View full text |Cite
|
Sign up to set email alerts
|

SAR202 Genomes from the Dark Ocean Predict Pathways for the Oxidation of Recalcitrant Dissolved Organic Matter

Abstract: Deep-ocean regions beyond the reach of sunlight contain an estimated 615 Pg of dissolved organic matter (DOM), much of which persists for thousands of years. It is thought that bacteria oxidize DOM until it is too dilute or refractory to support microbial activity. We analyzed five single-amplified genomes (SAGs) from the abundant SAR202 clade of dark-ocean bacterioplankton and found they encode multiple families of paralogous enzymes involved in carbon catabolism, including several families of oxidative enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
226
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(253 citation statements)
references
References 115 publications
26
226
1
Order By: Relevance
“…). Although some members of the SAR202 clade might be capable of fixing DIC (Yilmaz et al ., ) , previous studies indicated the heterotrophic lifestyle of SAR202 by utilizing recalcitrant as well as some labile organic compounds (Varela et al ., ; Landry et al ., ) which might explain the very low DIC uptake by SAR202 in this study (Fig. B).…”
Section: Discussionmentioning
confidence: 99%
“…). Although some members of the SAR202 clade might be capable of fixing DIC (Yilmaz et al ., ) , previous studies indicated the heterotrophic lifestyle of SAR202 by utilizing recalcitrant as well as some labile organic compounds (Varela et al ., ; Landry et al ., ) which might explain the very low DIC uptake by SAR202 in this study (Fig. B).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrospirae obtain energy from nitrite oxidation and members of this phylum have been shown to have extremely versatile metabolisms, which allow them to use CO 2 , organic compounds, perform aerobic hydrogen oxidation and even ammonia oxidation (Koch et al, 2015;Daims et al, 2015). Chloroflexi bacteria are also thought to be metabolically flexible (Yilmaz et al, 2015) and have the potential to use recalcitrant DOM compounds (Landry et al, 2017).…”
Section: Thaumarchaeota Marinimicrobiamentioning
confidence: 99%
“…Sinking particles are considered the main carbon source for bathypelagic communities (Nagata et al, 2000;Hansell and Ducklow, 2003), yet the flux of these particles is intermittent and variable on temporal and spatial scales (Arístegui et al, 2002;Arístegui and Montero, 2005). This frequent carbon scarcity seems to have led to the development of versatile metabolisms, as hinted by increasing findings of potential metabolic flexibility in deep ocean prokaryotes (Swan et al, 2011;Tang et al, 2016;Landry et al, 2017). However, the responses of deep ocean microbes to organic carbon starvation have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Their high abundance in the hadal metatranscriptome indicated that SAR202 bacteria were probably among the most active microbes in the hadal zone. SAR202 had been suggested to be involved in the degradation of recalcitrant dissolved organic matter (DOM) in a previous work (Landry et al ., ). Interestingly, transcripts of the recalcitrant DOM‐degrading genes of the hadal SAR202 MAGs were also highly abundant in the three hadal SAR202 MAGs (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, a cyclopentanol dehydrogenase transcript was associated with the highest FPKM value in MAG CH23. Cyclopentanol dehydrogenase in the SAR202 has been proposed to participate in the oxidation of a variety of cyclic alkanes, including sterol and hopanoid-like structures, to produce a more labile carboxylic acid (Landry et al, 2017). Labile DOM produced by the surface autotrophic planktons was largely degraded while they were falling into the deep oceans and only recalcitrant DOM was retained for further degradation (Hansell, 2013).…”
Section: Transcriptional Activities Of Hadal Microbesmentioning
confidence: 99%